Delayed Replantation of Avulsed Incisor with Prolonged Extraoral Dry Storage - Manju, M; L Shanthraj, Srinivas; Sethi, Natasha (Journal of Orofacial Research, 2015)
Trauma to the anterior teeth mainly affects children and adolescents. Tooth avulsion has become a common dental injury, that can occur at any age with maxillary anteriors being commonly affected. It affects the esthetics and psychological well being of both the child and the parent. Management of tooth avulsion in the permanent dentition often presents a challenge to the dental professional. Definitive treatment planning and consultation with specialists is seldom possible at the time of emergency treatment. Replantation of the avulsed tooth is an immediate procedure, which can restore the esthetics, function and create positive impact on patient if carried out under ideal conditions. This article describes the management of a patient with an avulsed maxillary permanent central incisor, that had been stored in unfavorable conditions for about 48 hours. Adequate space maintenance, esthetics and functional requirements of the patient were totally met till a long-term treatment is planned, when the patient finishes his pubertal growth.